Profesyonel ve Amatör Futbolcuların Hareket ve Reaksiyon Zamanlarının Karşılaştırılması - Ağaoğlu, Yavuz Selim (Ondokuz Mayıs Üniversitesi, Sağlık Bilimleri Enstitüsü, 1998)
ÖZET Bu çalışmada Türkiye'de profesyonel ve Amatör Futbolcular arasında sprint yeteneğinin belirleyici olup olmadığı belirlenmeye çalışıldı. Bunun için 5-10-20-30 m.'de hareket zamanlan ile ışık ve ses reaksiyon zamanlan ölçüldü. Profesyonel futbolcuların yaş genel ortalaması 24, boy genel ortalaması 175 cm. ve vücut ağırlıkları genel ortalaması 70 kg. iken, amatör futbolcuların yaş ortalaması 23, boy ortalaması 177cm ve vücut ağırlıkları ortalaması 70 kg olarak bulunmuştur. Ayrıca, profesyonel futbolcuların reaksiyon zamanları ortalamaları; ses 0.164 sn., ışık 0.175 sn. bulunmuş, amatörlerde ise ses 1.170 sn. ve ışık 0.177 sn. olarak bulunmuştur. Profesyonel ve amatör futbolcuların hareket zamanlan ortalamaları; Profesyonel futbolcuların 5 m. hareket zamanı; 0.94 sn Amatör futbolcuların 5 m. hareket zamanı; 0.89 sn Profesyonel futbolcuların 10 m. hareket zamanı; 1.57 sn Amatör futbolcuların 10 m. hareket zamanı; 1.55 sn Profesyonel futbolcuların 20 m. hareket zamanı; 2.94 sn Amatör futbolcuların 20 m. hareket zamanı; 3.07 sn Profesyonel futbolcuların 30 m. hareket zamanı; 4.12 sn Amatör futbolcuların 30 m. hareket zamanı; 4.16 sn Yapılan ölçümlerde, İstatiksel analize göre (ANOVA), profesyonel ve amatör futbolcular arasında önemli bir fark bulunmadı (P>0.05). Ayrıca profesyonel ve Amatör takım oyuncularının mevkilere göre karşılaştırılmasında önemli bir fark bulunmadı(P>0.05). IV

ABSTRACT In this study, it was tried to found sprinting speed was a determinant factor between professional and amateur football players. For this, 5m., 10m., 20m., 30m. of movement time and reaction time of football players were measured. While the values of professional football players as mean, in age was 24, in height was 175 cm and in weight was 70 kg, the values of amateur players as mean, in age was 23, in height was 177 and in weight was 70 kg were found. Morever, while the reaction time of professional players as mean of sound was 0.164 sn, light was 0.175sn, the amateur players values in sound was 0.170 sn and in light was 177 sn was found. Movement time of professional and amateur futbol players; Movement time of professional players in 5 m. was 0.94 sn. Movement time of Amateur players in 5 m. was 0.89 sn. Movement time of Professional players in 10 m. was 1.57 sn. Movement time of Amateur players in 10 m. was 1.55 sn. Movement time of Professional players in 20 m. was 2.94 sn. Movement time of Amateur players in 20 m. was 3.07 sn. Movement time of Professional players in 30 m. was 4.12 sn. Movement time of Amateur players in 30 m. was 4.16 sn. was found. At the measurement, according to Istatistical Analyss (ANOVA), the significant differences between professional and Amateur Football pleyars was not found. Morever, Football players of defence, offence and midfield between professionals and ameteurs were compared. According to Istatistical Analysis (ANOVA) no significant differences were found. Furthermore it was found that there was not significient difference between the position of the players.
Comparison of Movement and Reaction Time of Professional and Amateur Football Players
Tez (yüksek lisans) –Ondokuz Mayıs Üniversitesi, 1998
Libra Kayıt No: 31839
Keywords: Spor; Futbolcular; Reaksiyon Zamanı; Sports; Sürat; Football Players; Reaction Time; Speed; TEZ YÜK LİS A259p